Perinatal Outcomes Related to the Presence of a Nuchal Cord During Delivery: A Retrospective Cohort Study - Gabriel Viana Silva; Carolina Toledo Gontijo; Ana Paola Cruz Lunguinho; Mário Sérgio Gomes Caetano; Gustavo Yano Callado; Edward Araujo Júnior; Alberto Borges Peixoto (Diagnostics)
Objective: To evaluate and compare whether the presence of a nuchal cord (NC) and its characteristics had a negative impact on perinatal outcomes during delivery. Methods: This was a retrospective cohort study that analyzed the medical records of pregnant women from March 2020 to June 2023. Pregnant women were divided into groups with and without an NC. Singleton pregnancies ≥ 37 weeks were included, excluding fetal malformations, chromosomal anomalies, and cases with missing data and cord blood gas. Results: Of the 3364 medical records analyzed, 466 were included—366 without and 100 with an NC. Among the cases with an NC, 91% had one loop and 9% had ≥ two loops; 82% were loose and 18% were tight. Pregnant women with an NC had a higher gestational age (39.7 vs. 39.1 weeks, p = 0.006), fewer deliveries (1.0 vs. 2.0, p = 0.035), and a higher prevalence of cesarean sections (99% vs. 60.4%, p < 0.001). An NC was associated with a lower Apgar score at the 1st minute (8 vs. 9, p = 0.014) and higher arterial cord blood pH (7.27 vs. 7.24, p = 0.020). The presence of a tight cord was significantly associated with a 7.52-fold increased risk of an Apgar score < 7 at the 1st minute [x2(1) = 5.92, OR: 7.52, 95% CI: 1.51–37.31, R2 Nagelkerke: 0.14, p = 0.014]. Conclusions: There was no effect of the presence of an NC on adverse perinatal outcomes. However, the presence of a tight NC was associated with an increased risk of an Apgar score < 7 at the 1st minute, but no other effect on neonatal outcomes.